PROSES METABOLISME LIPID DALAM PERSPEKTIF AL-QUR’AN DAN HADIS - Daulay, Rabiah Afifa; Tarigan, Fanny Adha Cyntia; Okatiani, Puput; Nandhini, Saroza; Namiroh, Siti; Agustina, Tri (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2023)
Lipid metabolism is a process where fatty acids that enter the body are digested and then broken down as energi and later stored in the body for energi reserves. The lipids that we obtain as the main source of energi are neutral lipids, namely triglycerides (esters between glycerol and 3 fatty acids). This journal article aims to find out that lipid metabolism has a connection in the Qur'an and hadith. This research uses a qualitative approach through a case study of lipid metabolism from the Qur'anic perspective. The sources of research data are books, the Qur'an, and journals. In addition to these data sources, researchers also seek additional references from other data sources, namely a number of thesis literature, internet sources that are in accordance with the research. Lipid digestion results in the form of fatty acids and glycerol, some are still monoglycerides. As a result of it is water-soluble, glycerol enters the portal circulation (portal vein) of the liver. Other journal articles do not discuss the relationship between metabolism and the Qur'an and Al-Hadith, therefore this article can facilitate the relationship between the two, as stated in QS. Al-A'raf verse 31 and QS. Al-Mu'minunayat 21 which discusses fat content and lipid function.